Secukinumab in multi-failure psoriatic patients: the last hope?. (18th August 2018) - Magnano, M.; Loi, C.; Patrizi, A.; Sgubbi, P.; Balestri, R.; Rech, G.; Tasin, L; Girardelli, C. R.; Conti, A.; Odorici, G.; Campanati, A.; Offidani, A. M.; et al.
Abstract: Psoriasis is a multi-systemic chronic inflammatory disease that affects about 1.5–3% of the general population, of which almost 20% suffer from a moderate-severe form. Those patients can be treated with a systemic agent and in case of scarce response or contraindications, they may require a biologic therapy, such as tumor necrosis factor or interleukin-12/23 inhibitors. When also these agents fail, clinicians face a true therapeutic challenge. We report a case series of multi-failure 16 patients, successfully treated with secukinumab, a human monoclonal antibody that selectively neutralizes interleukin-17 A and is recently approved for the treatment of plaque psoriasis, psoriatic arthritis, and ankylosing spondylitis.